RANCANG BANGUN APLIKASI PENGIRIMAN BARANG PADA CV.PRIMA SEMESTA INTERNUSA BERBASIS ANDROID - Hendrokusumo, Ridzki; Sukmaaji, Anjik; Sutanto, Teguh (Jurnal Sistem Informasi Universitas Dinamika (JSIKA), 2020)
CV. Prima Semesta Internusa is one of the companies engaged in the field of freight forwarding and logistics. Through Prima Express's trade rights, it is one of the many companies whose services are delivering goods from Indonesian Workers (TKI) who work abroad to families in Indonesia. Since its establishment, the company has only one partner but over time the number of partner companies has increased. Therefore, the number of TKI goods that must be distributed also increases. This has an effect on the delivery time from the time the item is in the warehouse to the driver (courier) returning to the warehouse. So that the recapitulation of data and the making of reports by the administration for the counterparty is also getting longer. Based on the description above, it can be developed a design application for shipping goods on the CV. Prima Semesta Internusa is based on Android or Primex Mobile to help shorten business process time and minimize the occurrence of errors in the delivery of goods by the courier. From the results of the development to the Primex Mobile trial phase using the Black Box Testing method there are three test cases that are tested and the results are 100% successful. While testing using the Usability testing method gets a final value of 45 points from 50 points in total testing, it has concluded that Primex Mobile can run well and the company can shorten business time and minimize human error during company operations.Â Keywords: Delivery of goods, android, mobile.Â